(untitled) (CIPEEX, 2022)
CURRENTLY, WITH THE ADVENT OF TECHNOLOGY, MORE AND MORE MODERN TECHNOLOGIESARE AVAILABLE AND INNOVATIVE SOLUTIONS, WHETHER THROUGH SMARTPHONES, TABLETS ORCOMPUTERS, AND THESE ARE USED TO FACILITATE OUR DAY TO DAY, BOTH IN THE CITY AND INTHE COUNTRYSIDE. MAKE GOOD USE OF THE TECHNOLOGICAL RESOURCES THAT ARE AVAILABLE,CAN MAKE PROFESSIONALS, MAINLY IN AGRIBUSINESS, INCREASE THEIR PRODUCTIONEFFICIENCY, SAVE TIME AND GET THE BEST POSSIBLE FINANCIAL RETURN. IN THIS BIAS, IT ISNECESSARY POINT OUT THAT, THROUGH AGRO SAFARI, IT WILL BE POSSIBLE TO CARRY OUT MOREEASILY AND PRACTICALLY THE MANAGEMENT OF THE MAIN AGRIBUSINESS PROCESSESTHROUGH THE RESOURCES MADE AVAILABLE WITHIN THE PLATFORM. THUS, IN ORDER TOPROMOTE GREATER INTERACTION BETWEEN TECHNOLOGY AND AGRIBUSINESS, THE DISCIPLINEOF INTERDISCIPLINARY PRACTICE: PROCESS MANAGEMENT CONTRIBUTED TO THEPROBLEMATIZATION AND MANAGEMENT OF THE PROJECT, THE PROGRAMMING LABORATORYDISCIPLINE CONTRIBUTED TO THE DEVELOPMENT AND IMPROVEMENT OF THE PLATFORM ANDFINALLY THE DISCIPLINE OF ANALYSIS AND SOFTWARE DESIGN HELPED IN THE GATHERING OFREQUIREMENTS AND SCREEN PROTOTYPING.